2013
DOI: 10.1080/03036758.2013.825300
|View full text |Cite
|
Sign up to set email alerts
|

Early Miocene fossil frogs (Anura: Leiopelmatidae) from New Zealand

Abstract: The first pre-Quaternary anurans from New Zealand are reported from the Early Miocene (19Á 16 Ma) St Bathans Fauna based on 10 fossil bones. Four bones representing two new species differing in size are described in Leiopelma: Leiopelmatidae, and are the first Tertiary records for the family. Six indeterminate frog fossils are morphologically similar to leiopelmatids and represent two species consistent in size with those known from diagnostic material. These records are highly significant, as minimally, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…As noted by Waters and Craw (2006), the only certainty regarding this lineage is that it has gone extinct from other landmasses; current fossil data seem to shed little light on when these extinctions occurred. A similar case exists for the divergent NZ-endemic frog family Leiopelmatidae (Worthy et al, 2013) for which neither extant nor extinct sister lineages have been recorded from any other Southern Hemisphere landmass.…”
Section: Effects Of Sister-lineage Extinctionmentioning
confidence: 66%
See 1 more Smart Citation
“…As noted by Waters and Craw (2006), the only certainty regarding this lineage is that it has gone extinct from other landmasses; current fossil data seem to shed little light on when these extinctions occurred. A similar case exists for the divergent NZ-endemic frog family Leiopelmatidae (Worthy et al, 2013) for which neither extant nor extinct sister lineages have been recorded from any other Southern Hemisphere landmass.…”
Section: Effects Of Sister-lineage Extinctionmentioning
confidence: 66%
“…The finding of diverse biological lineages in NZ's Miocene fossil record has often been interpreted as evidence for the persistence of Zealandia's biota throughout the Oligocene (Kaulfuss, Brown, Henderson, Szwedo, & Lee, 2018;Kaulfuss et al, 2015;Worthy, Tennyson, & Scofield, 2011;Worthy, Tennyson, Scofield, & Hand, 2013). Worthy et al (2013), for instance, noted that "all the key elements" of NZ's modern terrestrial biota were in place only 4 mya after the maximum Oligocene inundation and concluded that these data likely supported vicariant origins for these Miocene lineages.…”
mentioning
confidence: 99%
“…Recent discoveries of 16–19 Myr old novel species of frog closest to Leiopelma also suggest an ancient and diverse fauna that probably pre‐date the Oligocene (Worthy et al ., ). One of these new species, L. miocaenale , appears closest to the recently extinct toad forms, while another, L. acricarina , may be sister to all the other taxa.…”
Section: Discussionmentioning
confidence: 97%
“…It will be particularly interesting to obtain DNA from the latter two to assess their true affinity, their antiquity and their place in the pre-human New Zealand ecosystem. Recent discoveries of 16-19 Myr old novel species of frog closest to Leiopelma also suggest an ancient and diverse fauna that probably pre-date the Oligocene (Worthy et al, 2013). One of these new species, L. miocaenale, appears closest to the recently extinct toad forms, while another, L. acricarina, may be sister to all the other taxa.…”
Section: Discussionmentioning
confidence: 97%
“…The region had a rich diverse fauna and flora (e.g. Worthy, Tennyson & Scofield, ; Worthy et al ., ), with reported monocot macrofossils including palms (Pole, ), Ripogonum (Pole, ) and long‐stalked Ruppia ‐like endocarps, which were described originally as possible long‐awned grass fruits (Pole, ). Pole () also sampled dispersed cuticle from 120 drill cores in the Manuherikia Basin and Southland Coalfield, finding 15 monocot morphotypes, mostly unidentified, but which he regarded as probably representing semi‐aquatic macrophytes.…”
Section: Discussionmentioning
confidence: 99%